Mean platelet volume and red cell distribution width levels in initial evaluation of panic disorder - Asoglu M; Aslan M; Imre O; Kivrak Y; Akil O; Savik E; Buyukaslan H; Fedai U; Altındag A (Neuropsychiatric Disease and Treatment, 2016)
Mehmet Asoglu,1 Mehmet Aslan,2 Okan Imre,1 Yuksel Kivrak,3 Oznur Akil,1 Emin Savik,4 Hasan Buyukaslan,5 Ulker Fedai,1 Abdurrahman Altındag6 1Department of Psychiatry, Faculty of Medicine, Harran University, Sanliurfa, 2Department of Internal Medicine, Faculty of Medicine, Yuzuncu Yil University, Van, 3Department of Psychiatry, Faculty of Medicine, Kafkas University, Kars, 4Department of Clinical Biochemistry, Faculty of Medicine, Harran University, 5Department of Emergency Medicine, Faculty of Medicine, Harran University, Sanliurfa, 6Department of Psychiatry, Faculty of Medicine, Gaziantep University, Gaziantep, Turkey Background: As the relationship between psychological stress and platelet activation has been widely studied in recent years, activated platelets lead to certain biochemical changes, which occur in the brain in patients with mental disorders. However, data relating to the mean platelet volume (MPV) in patients with panic disorder (PD) are both limited and controversial. Herein, we aimed to evaluate, for the first time, the red cell distribution width (RDW) levels combined with MPV levels in patients with PD.Patients and methods: Between January 2012 and June 2015, data of 30 treatment-naïve patients (16 females, 14 males; mean age: 37±10 years; range: 18–59 years) who were diagnosed with PD and 25 age- and sex-matched healthy volunteers (10 females, 15 males; mean age: 36±13 years; range: 18–59 years) (control group) were retrospectively analyzed. The white blood cell count (WBC), MPV, and RDW levels were measured in both groups.Results: The mean WBC, MPV, and RDW levels were 9,173.03±2,400.31/mm3, 8.19±1.13 fl, and 12.47±1.14%, respectively, in the PD group. These values were found to be 7,090.24±1,032.61, 6.85±0.67, and 11.63±0.85, respectively, in the healthy controls. The WBC, MPV, and RDW levels were significantly higher in the patients with PD compared to the healthy controls (P=0.001, P=0.001, and P=0.003, respectively). However, there was no significant difference in the platelet number between the patients with PD and healthy controls (P>0.05).Conclusion: Our study results are the first to demonstrate that the RDW levels combined with MPV levels significantly increase among patients with PD. We believe that increased RDW and MPV levels can be used as a novel marker for PD. Keywords: panic disorder, mean platelet volume, red cell distribution width, white blood cell count, platelet number